Profile Number Sense of 5th Grade Students Subject Based on Field-Dependent and Field-Independent Cognitive Style - Mariana, Risa; Khabibah, Siti; Amin, Siti Maghfirotun (Universitas Malikussaleh, 2020)
Number sense can vary from person to person, number sense variations can be caused by learning experiences of mathematics, mathematical abilities, and cognitive styles. This research is a qualitative descriptive study that aims to determine the number sense profile of grade V SD students in terms of the field-dependent and field-independent cognitive styles on fraction material. So the research begins by giving a math ability test, cognitive style test, and number sense test. The subjects of this study were fifth-grade students of SDN Ngagel Rejo V Surabaya with field-dependent and field-independent styles with equivalent math abilities. Data collection was continued with the number sense test, and interviews and checks using time triangulation. The results showed that students with a field-independent cognitive style tended to use logical reasoning and actively processed information and were able to simplify complex problems well. They also have a high of number sense so that they can answer and describe answers based on their analytical skills. For example, when comparing the concept of numbers, they can show that there is another fraction or decimal between two fractions or decimals. Whereas students in the field-dependent cognitive style only compare the values of the two fractions or decimals, which means they have difficulty separating and distinguishing objects. simple of complex objects. They also tend to do conventional learning such as doing multiplication using a pencil and writing on paper and cannot analyze a thing or question with an estimate or approach. Therefore, students' cognitive styles must be learned and aligned with existing teaching strategies in several schools. Teaching adjustments that are in line with students' cognitive styles are needed to improve student performance.